IDNLearn.com connects you with a community of knowledgeable individuals ready to help. Our platform offers reliable and detailed answers, ensuring you have the information you need.

You are given the exponential function g(x)=3^x. Which ootion below gives the formula for the new function h created by stretching g by a factor of 3 along the y-axis?

Sagot :

Answer:

h(x) = 3^(x + 1)

Step-by-step explanation:

The exponential function is;

g(x) = 3^(x)

Now, in transformation of exponential functions of say f(x) = b^(x), when the new function g(x) is created by stretching by a factor of say c along the y-axis, we have;

g(x) = c•b^(x)

In this question, we are told it is stretched by a factor of 3 along the y-axis.

Thus, new function h is;

h(x) = 3 × 3^(x)

Using law of indices, we have;

h(x) = 3^(x + 1)